2017
DOI: 10.1111/bjh.14954
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic cell transplantation for blastic plasmacytoid dendritic cell neoplasm: a North American multicentre collaborative study

Abstract: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is incurable with conventional therapies. Limited retrospective data have shown durable remissions after haematopoietic cell transplantation (HCT) [allogeneic (allo) or autologous (auto)]. We conducted a multicentre retrospective study in BPDCN patients treated with allo-HCT and auto-HCT at 8 centres in the United States and Canada. Primary endpoint was overall survival (OS). The population consisted of 45 consecutive patients who received an allo-HCT (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 20 publications
3
46
2
2
Order By: Relevance
“…Although several reports have revealed that patients with BPDCN normally responded well with initial chemotherapy, unfortunately, the patient of our case responded the other way. Even after several cycles of intensive chemotherapies.…”
Section: Discussioncontrasting
confidence: 68%
“…Although several reports have revealed that patients with BPDCN normally responded well with initial chemotherapy, unfortunately, the patient of our case responded the other way. Even after several cycles of intensive chemotherapies.…”
Section: Discussioncontrasting
confidence: 68%
“…6,7 Allo-HSCT therapy is more effective than autologous HSCT therapy. 8 In recent years, other treatments have been used for BPDCN, especially for recurrent/refractory (R/R) patients. These new treatments and clinical trials for R/R BPDCN patients included Elzonris (tagraxofusp SL-401), which targets CD123 on tumor cells regardless of primary patients or R/R patients, 9 daratumumab, which targets CD38 on tumor cells for only a few patients, 10 pralatrexate, which is used for progression of BPDCN, 11 venetoclax, which promotes tumor cell apoptosis, 12 bortezomib, which downregulates NF-kB activity, 13 and 5ʹ-azacytidine, which reduces tumor cell methylation levels.…”
Section: Discussionmentioning
confidence: 99%
“…Protocol for ALL includes prophylaxis of the nervous system with intrathecal chemotherapy, since it is considered one of the main causes of morbidity and mortality in patients with this disease 7 . Bone marrow transplantation is usually reserved for cases with one or multiple relapses; in elderly patients is also used as a consolidation therapy after chemotherapy 8,11,13 . However, in pediatric patients it does not improve survival 2 .…”
Section: Discussionmentioning
confidence: 99%